(3EYQGH GdbQBfs - (3GdRLGL , EHQGgje Hf GdSQj Hf Sgd, CHhESMGb,J (B311 (3g` s
(3ChdgG (B:s
(3bhdg (B((3heG Cgd dZjQ Gddg Hg (B)(3ef ShQg GdeGFOg s
(3BNQgG (B:s
(3jfJgi YfO Ghd EYQGH bhdg JYGdi (B((3Ke HOdfG ecGf GdSjFg GdMSfg (B) (3hgPg gi GdBjg (B95 (3ef ShQg GdCYQGa hjHOG GdeLdO GdNGeS HEYQGH GdBjg (B97 (3ajchf GdfGbU gh EYQGH GdBjg (B96 s
(3GdLRA GdSGHY YTQ GdSGbW jJVef EYQGH bhdg JYGdi (B" (3hcJHfG Ydjge ajgG Cf dfaS HGdfaS (B" (3Edi BNQ bhdg JYGdi (B" (3hbO SCdgG bhe ef bHdce Ke CUHMhG HgG cGaQjf (B"s
(3GdLRBf GdKGef YTQ hGdhGMO hGdYTQhf cJHG HNW eZGjQ hdcfg CfOdSi hbOje CjVkGs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B40 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B33s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs